Development of construction materials from the geopolymerization of red clay and coal fly ash - Pathak, Arvind; Ranjit, Arpana; Dhakal, Bijaya (BIBECHANA, 2022)
Red clay contains solid aluminosilicate has been shown to be reactive in the presence of an alkaline activator. The addition of coal fly ash and lime has shown improvements in their mechanical and physical properties of the geopolymer products. FTIR analysis and SEM images of the product have shown the formation of aluminosilicate gel in the geopolymeric product. The maximum compressive strength of the geopolymer products GP-RFL was achieved to be 15.92 N/mm2 having water absorption of 10.47 % and bulk density 2.81 g/cm3. These results indicated that geopolymer mortars made from red clay, coal fly ash and lime could be used as an alternative construction material./p>BIBECHANA 19 (2022) 119-126